Transformasi Sosial-Ekonomi dalam Era Ekonomi Digital: Analisis Sosiologi Ekonomi terhadap Dinamika Platform Online - Ciek Julyati Hisyam; Zakiyah Rodja; Nuraini Salsabila; Nadya Patricia Lubis (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
This research aims to analyze the socio-economic transformations that occur in the digital economy era, with a focus on Various techniques and methods that have been described by the author in various literatures, journals, papers, and other publications have been researched and identified. The qualitative method was chosen because it is considered the most suitable approach to explore and understand phenomena as well as answer the questions that arise. Using an economic sociology approach, this study explores how social interactions, economic structures, and consumption patterns are changing along with the development of digital technologies and online platforms. The results show that online platforms not only change the way they transact and do business, but also affect social relations, economic stratification, and social mobility. The platform provides new opportunities for economic inclusion and wider participation in the market, but also poses challenges related to digital inequality and labor exploitation. Thus, this research contributes to understanding the socio-economic implications of digital transformation and provides insight for the development of more inclusive and equitable policies in the digital economic era.